A customer-involved design concept evaluation based on multi-criteria decision-making fusing with preference and design values. (October 2021) - Qi, Jin; Hu, Jie; Peng, Yinghong
Abstract: Customer-involved design concept evaluation (CDCE) is a key issue for developing new product welcomed by customers, but seldom studies have considered the integrated utilization of objective design values (DVs) and customers' subjective preference values (PVs). Our previous study has attempted to fuse with DVs and PVs in CDCE, while this is only limit to few situations under benefit-like and cost-like evaluation criteria. For better CDCE, this study further fuses with DVs and PVs in more complex situations, and puts forward an improved version of rough distance to redefined ideal solution (RD-RIS II) in multi-criteria decision-making (MCDM) scope to select the optimal concept. Different from old RD-RIS in previous study, RD-RIS II not only supports the ideal solution definition (ISD) processes for both quantitative and qualitative evaluation criteria, and but more importantly, it utilizes more useful information (value, feature, number and impact) from DVs and PVs to redefine the new positive ideal solution (PIS) and negative ideal solution (NIS). Through the rough distance calculation, the alternative which is close to PIS and far away from NIS is selected as the best one. Besides, the feasibility of RD-RIS II is validated via the application in real design evaluation example, and three empirical comparisons confirm that RD-RIS II makes more comprehensive decision than other MCDM-based evaluation methods, especially when the choices of customers and designers are conflicting, therefore it could provide more reasonable evaluation result which has better credibility and stability than others.